History and Application of Piercing the Corporate Veil Doctrine: A Comparison Study between the United Kingdom and Indonesia - Kamaluddin, Muhammad Aqil (Universitas Airlangga, 2025)
Separate legal entity doctrine is a foundation in corporation law, and courts have generally resisted deviations from it, save in specific instances involving doctrine of piercing of the corporate veil (PCV). PCV doctrine permits a party to circumvent the separate legal personality and hold the company's